Effects of potassium salts loading on calcium oxide on the hydrogen production from pyrolysis-gasification of biomass. (February 2018) - Yang, Haiping; Wang, Daqian; Li, Bin; Zeng, Zhiwei; Qu, Lei; Zhang, Wennan; Chen, Hanping
Highlights: Effects of K salts loading on CaO on straw pyrolysis-gasification were studied. 0.25 wt% KCl enhanced CO2 absorption of CaO and 0.25 wt% K2 CO3 /K2 SO4 inhibited. More KCl loading reduced CO2 absorption of CaO and raised catalytic effect of KCl. 0.25 wt% KCl loading greatly improved the cyclic H2 production performance of CaO. Abstract: The effects of potassium (K) salts loading on CaO on the H2 production from pyrolysis-gasification of wheat straw were investigated. The loading of 0.25 wt% KCl could significantly enhance the CO2 absorption capability of CaO. The CO2 concentration in the product gas decreased sharply from 20.83 to 11.70 vol%, and the H2 concentration increased from 48.2 to 55.5 vol%. While the loading of 0.25 wt% K2 CO3 /K2 SO4 inhibited the enhancing effect of CaO. Further increasing the loading of KCl on CaO, the CO2 absorption of CaO declined, but the catalytic effect of KCl on the gasification process was promoted. The loading of 0.25 wt% KCl on CaO significantly improved the cyclic performance of CaO during the pyrolysis-gasification process. Higher H2 concentration and more CO2 absorbed by CaO were obtained with the loading of 0.25 wt% KCl even after 5 cycles compared with those of pure CaO in the first cycle.